Attenuation of Live-Attenuated Yellow Fever 17D Vaccine Virus Is Localized to a High-Fidelity Replication Complex - Emily H. Davis (American Society for Microbiology, 2019)
ABSTRACT The molecular basis of attenuation for live-attenuated vaccines is poorly understood. The yellow fever (YF) 17D vaccine virus was derived from the wild-type, parental strain Asibi virus by serial passage in chicken tissue and has proven to be a very safe and efficacious vaccine. We have previously shown that wild-type Asibi is a typical RNA virus with high genetic diversity, while the 17D vaccine virus has very little genetic diversity. To investigate this further, we treated Asibi and 17D viruses with ribavirin, a GTP analog with strong antiviral activity that increases levels of mutations in the viral genome. As expected, ribavirin treatment introduced mutations into the Asibi virus genome at a very high frequency and decreased viral infectivity while, in contrast, the 17D vaccine virus was resistant to ribavirin, as treatment with the antiviral introduced very few mutations into the genome, and viral infectivity was not lost. The results were confirmed for another YF wild-type parental and vaccine pair, a wild-type French viscerotropic virus and French neurotropic vaccine. Using recombinant Asibi and 17D viruses, ribavirin sensitivity was located to viral nonstructural genes. Thus, two live-attenuated YF vaccine viruses are genetically stable even under intense mutagenic pressure, suggesting that attenuation of live-attenuated YF vaccines is due, at least in part, to fidelity of the replication complex resulting in high genetic stability. IMPORTANCE Live-attenuated viral vaccines are highly safe and efficacious but represent complex and often multigenic attenuation mechanisms. Most of these vaccines have been generated empirically by serial passaging of a wild-type (WT) virus in cell culture. One of the safest and most effective live-attenuated vaccines is yellow fever (YF) virus strain 17D, which has been used for over 80 years to control YF disease. The availability of the WT parental strain of 17D, Asibi virus, and large quantities of clinical data showing the effectiveness of the 17D vaccine make this WT parent/vaccine pair an excellent model for investigating RNA virus attenuation. Here, we investigate a mechanism of 17D attenuation and show that the vaccine virus is resistant to the antiviral compound ribavirin. The findings suggest that attenuation is in part due to a low probability of reversion or mutation of the vaccine virus genome to WT, thus maintaining a stable genotype despite external pressures.